Musicoterapia na promoção da saúde: um cuidado para a qualidade de vida e controle do estresse acadêmico - Panacioni, Graziela França Alves (2012)
Stress is a part of people’s daily lives and is influenced by many factors. Entering academic life can increase stress levels and generate physical and/or psychological symptoms that affect students’ quality of life and health. The aim of this research, which used qualitative and quantitative methodology, was to investigate the effect of music therapy in stress management for a group of undergraduate and graduate students and investigate the effect of music therapy on the quality of life of these subjects. We included undergraduate and graduate students at UFG, aged 18 years and older, who showed some level of stress on Lipp’s Stress Symptoms Inventory - LSSI (Lipp, 1996),. The subjects were referred to the research program through UFG’s Saudavelmente Program linked to the Social Service Division of PROCOM – the Office of the Dean of Academic Affairs, after approval by the university’s Ethics Committee. Qualitative data were collected using socio-demographic questionnaires, music therapy forms, semi-structured interviews, reports and audios and videos of the sessions. LSSI and WHOQOL-Bref (for assessment of quality of life), were used for collecting quantitative data. Both were administered by a psychologist involved in the research before and after the music therapy sessions. We established a closed group of nine students who participated in ten music therapy sessions lasting from sixty to ninety minutes and used the musical experiences described by Bruscia (2000). In the music therapy process, it was possible to work on strategies for coping with stress such as increasing self-esteem, decreasing anxiety, time management, life goal setting and improving intra-and interpersonal relationships. For music therapy sessions, songs related to the participants’ sound and musical identity were used. Music therapy analysis of the sessions was carried out leading to a discussion from the phenomenological point of view of the therapeutic process which went on, excerpts from interviews and the quantitative results. The results show that music therapy can contribute to health promotion, stress management and to an improvement in students’ the quality of life. In conclusion, the participation of a music therapist in multidisciplinary programs for students can help build a healthier university.